Challenging the Groupthink of the Guild. Issue 3 (July 2016) - Warsh, Kevin
Abstract The fall in global nominal GDP growth from the precrisis period to the post-crisis period is alarming. Economic policymakers, including central bankers, failed to deliver the economic outcomes that they promised. Monetary policy, in particular, is not readily reducible to a set of immutable truths. Too many in the professoriate rely to our detriment on the outputs of their preferred models. I am troubled by Fed fine-tuning of policy and overpromising of benefits. Measurement challenges are growing faster than our understanding of inflation dynamics. The Fed is preoccupied with its vaunted forecasts. Instead, it should focus its considerable energies on more troubling contemporaneous developments in the real economy.